2013 Evaluation of In-Furrow and Foliar Fungicides for Disease Control in Peanut in Jay, Florida - Darcy E. P. Telenko; John Atkins; Nick Dufault (EDIS)
This 10-page fact sheet summarizes the 2013 in-furrow and foliar fungicide programs for control of early and late leaf spot and white mold (southern stem rot) of peanut in Jay, Florida. It shows the effectiveness of 13 fungicide programs for disease control, as compared to no treatment. This data represents only one year and one location, and readers are cautioned that test results should be considered over several locations and years before final conclusions are valid. Written by Darcy E. P. Telenko, John Atkins, and Nick Dufault, and published by the UF Department of Plant Pathology, January 2014.